GPR40 activation alleviates pulmonary fibrosis by repressing M2 macrophage polarization through the PKD1/CD36/TGF-β1 pathway - Wan Hui-qi; Xie Ling-feng; Li Hong-lin; Ma Yan; Li Qiu-hui; Dai Meng-qing; Fu Yuan-dong; Li Wen-jun; Zhou Jin-pei; Qian Min-yi; Shen Xu (Acta Pharmacologica Sinica, 2025)
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive interstitial lung disease characterized by complex aetiologies involving the accumulation of inflammatory cells, such as macrophages, in the alveoli. This process is driven by uncontrolled extracellular matrix (ECM) deposition and the development of fibrous connective tissues. Here, we observed that the mRNA expression of Ffar1, the gene encoding G protein-coupled receptor 40 (GPR40), is repressed, while Cd36 is increased in the bronchoalveolar lavage fluid (BALF), which is predominantly composed of alveolar macrophages, of IPF patients. Furthermore, the GPR40 protein was found to be largely adhered to macrophages and was pathologically downregulated in the lungs of bleomycin (BLM)-induced PF model mice (PF mice) compared with those of control mice. Specific knockdown of GPR40 in pulmonary macrophages by adeno-associated virus 9-F4/80-shGPR40 (AAV9-shGPR40) exacerbated the fibrotic phenotype in the PF mice, and activation of GPR40 by its determined agonist compound SC (1,3-dihydroxy-8-methoxy-9H-xanthen-9-one) effectively protected the PF mice from pathological exacerbation. Moreover, Ffar1 or Cd36 gene knockout mouse-based assays were performed to explore the mechanism underlying the regulation of GPR40 activation in pulmonary macrophages with compound SC as a probe. We found that compound SC mitigated pulmonary fibrosis progression by preventing M2 macrophage polarization from exerting profibrotic effects through the GPR40/PKD1/CD36 axis. Our results strongly support the therapeutic potential of targeting intrinsic GPR40 activation in pulmonary macrophages for IPF and highlight the potential of compound SC in treating this disease.